MASS-4 is more suitable than MASS-3 for prognostic stratification in transplant-eligible patients with newly diagnosed multiple myeloma - Fan Yang; Junru Liu; Jingli Gu; Meilan Chen; Beihui Huang; Lifen Kuang; Juan Li (Annals of Medicine, 2025)
Objectives Real-world studies have shown that Mayo Additive Staging System (MASS) −3 and MASS-4 are suitable for prognostic stratification in Chinese patients with newly diagnosed multiple myeloma (NDMM), but there is no clear evidence of their utility in transplant-eligible NDMM patients. We aimed to evaluate and compare the prognostic stratification value of MASS-3 and MASS-4 in transplant-eligible patients with NDMM in China.Patients and Methods A retrospective analysis of the clinical data of 215 NDMM patients who received ‘induction therapy-autologous hematopoietic stem cell transplantation (ASCT)’ in our center from 2013 to 2022 was performed. The prognostic stratification value of the two staging techniques was compared in terms of patient’s overall survival (OS) and progression free survival (PFS), using different transplant times, different ages, and different induction regimens.Results The median progression-free survival (PFS) was 99, 88, and 51 months (p = 0.010), and the median overall survival (OS) was not reached, 110, and 80 months (p = 0.003) in MASS-3 I, II, and III patients, respectively. The median PFS was 99, 88, 53, and 35 months (p = 0. 002), and the median OS was not reached, 110, 106, and 41 months (p < 0.001) for patients in MASS-4 I, II, III, and IV, respectively. And MASS-4 can identify patients with poor prognosis among the Revised International Staging System (R-ISS) stage II patients. In patients with single ASCT, different ages, and different induction regimens, the prognostic stratification of MASS-4 was also better than that of MASS-3. However, there was no significant difference in PFS and OS between different MASS-3 or MASS-4 stages in patients with tandem ASCT.Conclusions Among transplant-eligible patients with NDMM, the prognostic stratification value of MASS-4 was better than that of MASS-3, particularly distinguishing high-risk patients with poor prognosis. Compared with single ASCT, tandem ASCT may overcome the poor prognosis of high-risk MASS patients.